The Normative Data for Sensorineural Acuity Level (SAL) Test among Young Adults: Comparisons Between B71 and B81 Bone Transducers - Awang, Mahamad Almyzan; Mohd Don, Ainul Hazwani; Salim, Rosdan; Sul’ain, Mohd Dasuki; Zakaria, Mohd Normani (International Journal of Statistics in Medical Research, 2021)
Introduction: The sensorineural acuity level (SAL) test is a valuable clinical assessment for hearing diagnosis, especially when the results of pure tone audiometry (PTA) are incomplete or questionable. Nevertheless, the literature on the SAL test is extremely limited and more research efforts are warranted to promote the application of this test in clinical settings. Essentially, the aim of the present study was to compare the normative data for the SAL test between two different bone vibrators (Radioear B71 and Radioear B81) among Malaysian participants. Materials and Methods: Forty-two healthy Malaysian adults (aged 19 to 27 years) participated in this repeated-measures study. The PTA and SAL test was carried out according to the recommended protocols. The SAL normative data produced by the two bone transducers were then compared at different frequencies. Paired t-test and Bayesian inference were used for data analyses. Results: The normative data for the SAL test gathered in the present study were descriptively higher than those reported among Caucasian adults. Relative to the Radioear B81 bone vibrator, the SAL normative data were significantly higher for the Radioear B71 bone transducer at all tested frequencies (p < 0.001, BF10 ≥ 48.67). Conclusions: The SAL normative data established by the two bone vibrators are statistically different. This information would be beneficial to provide clinicians with appropriate normative data when performing the SAL test on Malaysian patients.